Strategi Komunikasi Hokben Cimahi Dalam Meningkatkan Brand Awareness - Dede Rusmiati; Yogie Alontari (KOMVERSAL, 2024)
Communication Strategy is a very valuable science for doing a business both individually and in companies. And this communication strategy really helps the business process to be better and develop. In this study, it found a phenomenon in one of the companies, namely Hokben Cimahi, which experienced a decrease in customer visits after the occurrence of covid 19, So that researchers are interested in discussing more deeply why HokBen Cimahi experienced a decrease in visitors, based on the information obtained and also as an employe in HokBen Cimahi, Researchers are interested in a discussion related to communication strategies in HokBen Cimahi., this is related to the phenomenon applied in HokBen Cimahi about how communication strategies are used to increase brand awareness. Hokben Cimahi is located in area / city Jl. Jend. H. Amir Machmud NO 304 ,North Cimahi District, Cimahi City, West Java. In this study using qualitative research methods aimed at describing regularly in the focus of this study, entitled "HOKBEN CIMAHI COMMUNICATION STRATEGY IN INCREASING BRAND AWARENESS". The result of this study is that the communication strategy in increasing brand awareness at Hokben Cimahi is very instrumental and has a good impact in increasing visitors and sales. The communication strategy is applied to have a role of reminder for consumers regarding the existence and information of products, introduce products and services in Hokben Cimahi, and also maintain consumer loyalty or customers